Optimization of Nutrition Counse Optimalisasi Konseling Gizi Melalui Media Sosial Whatsapp Terhadap Perubahan Pola Makan Pasein DM Tipe 2 Di RSUD Tengku Rafi’an Siak - Ismed Ismed; Warsono (POLTEKKES KEMENKES MEDAN, 2023)
Diabetes Mellitus is one of the ten biggest diseases hospitalized at RSUD Tengku Rafi'an Siak. In February 2022, the number of visits for diabetes mellitus (DM) patients was 144 people, and in March it increased to 161 people. The increase in the number of DM sufferers is mainly caused by the development of the wrong diet. The purpose of the study was to determine the effectiveness of nutritional counseling on the diet of Type 2 Diabetes Mellitus patients. The type of research is quantitative with a queasy experiment research design and a non-randomized control group pretest-posttest design. This research was carried out at RSUD Tengku Rafi'an Siak in May-July 2022. The intervention group received face-to-face counseling 4 times and through Whatsapp groups 4 times. The control group only received face-to-face counseling 4 times. The number of respondents for each group was 30 people. The variables collected were diet and nutritional knowledge. Data analysis was performed with non-parametric Wilcoxon and Mann-Whitney. The results of this study showed a change in eating pattern scores for the better (-89.3±30.2) in the intervention group, on the contrary, there was an increase in eating pattern scores (6.2±61.0) in the control group after education was given. There was a significant increase in nutritional knowledge in the intervention group (19.2±9.25) compared to controls (8.7±4.42) after the education was given. Face-to-face nutrition counseling accompanied by counseling through Whatsapp groups is effective in increasing knowledge and improving the diet of Type 2 Diabetes Mellitus patients at RSUD Tengku Rafi'an Siak except for vegetables. It is expected for Tengku Rafian Siak Hospital to use nutritional counseling and reminders via WhatsApp social media to DM patients.